Pancasila Philosophy as a Basis for Strengthening Religious Moderation in Indonesia - Tantra, Manggala Wiriya; Santoso, Heri; Agus Siswadi, Gede (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2024)
The development of religious fanaticism that is not in accordance with the constitution and state ideology is certainly very dangerous. The current government has promoted a program to strengthen religious moderation as a strategic step taken. However, the source of strengthening religious moderation is considered still minimal to bring up Pancasila as a basic value as well as the philosophy of the Indonesian nation. Whereas Pancasila is a guideline for the life of the Indonesian nation that shapes the character and character and personality of the nation. The purpose of this research is to present the values of Pancasila as the basis for strengthening religious moderation in Indonesia. This qualitative research method is a literature study using a philosophical normative approach. This literature research optimizes references about Pancasila and strengthening religious moderation in Indonesia. The results of the research present Pancasila which is very rich in values that are a source in strengthening religious moderation. Key values in religious moderation are found to be very diverse and very rich in the formulation of Pancasila. The power of Pancasila as a source of strengthening religious moderation can strengthen and strengthen Indonesian society in moderate religion.